2020
DOI: 10.1021/acsomega.0c00339
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Leaching Kinetics of Vanadium from the Vanadium-Chromium-Reducing Residue with K2Cr2O7

Abstract: Oxidative-alkaline leaching of vanadium from vanadiumchromium-reducing residues with K 2 Cr 2 O 7 was investigated in this paper. The effects of processing parameters including dosage of NaOH, dosage of K 2 Cr 2 O 7 , reaction time, and reaction temperature on the leaching efficiency of vanadium were studied. The results simulated by response surface methodology indicated that vanadium leaching was affected significantly by the dosage of K 2 Cr 2 O 7 and NaOH, and the processing parameters that affected the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The interactions between the experimental parameters were important for the experimental results, which were ignored during the single-factor experiment; thus, RSM was applied to optimize the experimental process and order the significance of the experimental parameters [13,29,30]. In this paper, the experimental parameters that affected the reduction process were selected as A (m (C)/m(Cr)), B (reaction temperature), C (reaction time), and D (concentration of H 2 SO 4 ).…”
Section: Response Surface Optimizationmentioning
confidence: 99%
“…The interactions between the experimental parameters were important for the experimental results, which were ignored during the single-factor experiment; thus, RSM was applied to optimize the experimental process and order the significance of the experimental parameters [13,29,30]. In this paper, the experimental parameters that affected the reduction process were selected as A (m (C)/m(Cr)), B (reaction temperature), C (reaction time), and D (concentration of H 2 SO 4 ).…”
Section: Response Surface Optimizationmentioning
confidence: 99%
“…The interactions between experimental parameters were important for the experimental results while it had been ignored during the single factor experiment, thus, RSM was applied to optimize the experimental process and order the significance of experimental parameters [13,29,30]. In this paper, the experimental parameters affected the reduction process were selected as A (m (C)/m(Cr)), B (Reaction Temperature), C (Reaction Time) and D (Concentration of H2SO4).…”
Section: Response Surface Optimizationmentioning
confidence: 99%
“…The main reaction during the reduction process was between chromium and oxalic acid. The △G of main reactions were calculated at 298 K [21][22][23] . The results displayed in Figure 1b showed that the △G was negative, which indicated that the reduction of Cr (VI) with oxalic acid was feasible in thermodynamic.…”
Section: Resultsmentioning
confidence: 99%